2014
DOI: 10.1684/ejd.2013.2243
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between cutaneous IgM deposition and renal involvement in adult patients with Henoch-Schönlein purpura

Abstract: Background: Henoch-Schönlein purpura (HSP) is a systemic and immune complex-related leukocytoclastic vasculitis. A positive correlation has been found between IgM deposition along with IgA in skin lesions diagnosed by direct immunofluorescence (DIF) and renal involvement with HSP. Objectives: We sought to investigate the relationship between the systemic associations of the disease and the severity of the skin lesions, as well as the immune deposition findings of the lesional skin provided by DIF in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
2
11
2
2
Order By: Relevance
“…Both the absence of these co-existing diseases and the lower rate of deep-organ involvement seem to indicate a better prognosis. This conflicts with a recent report by Belli et al, who in their description of 47 Turkish patients found a significant relationship between frequency of bullous and necrotic lesions and the development of gastrointestinal and renal involvement in HSP [15]. They also note an association with IgM and renal involvement, although Poterucha et al have previously argued against such a relationship in their cohort [12].…”
Section: Discussioncontrasting
confidence: 56%
“…Both the absence of these co-existing diseases and the lower rate of deep-organ involvement seem to indicate a better prognosis. This conflicts with a recent report by Belli et al, who in their description of 47 Turkish patients found a significant relationship between frequency of bullous and necrotic lesions and the development of gastrointestinal and renal involvement in HSP [15]. They also note an association with IgM and renal involvement, although Poterucha et al have previously argued against such a relationship in their cohort [12].…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, Barnadas et al found IgA to be the most frequently detected immunoglobulin in LCV patients overall, and showed its association with renal involvement . Nevertheless, in 2 previously reported studies, IgM deposition was found to be associated with a higher risk of renal involvement, primarily in adult patients; however, these findings were not reproducible in children . Importantly, in this study, the presence of immunoreactants other than IgA in the setting of histologically confirmed LCV did not seem to predict systemic or persistent disease, although the number of cases with IgG or IgM immunoreactivity was low.…”
Section: Discussioncontrasting
confidence: 44%
“…Similarly, Barnadas et al found IgA to be the most frequently detected immunoglobulin in LCV patients overall, and showed its association with renal involvement. 6 Nevertheless, in 2 previously reported studies, IgM deposition was found to be associated with a higher risk of renal involvement, primarily in adult patients 12,13 ; however, these findings were not reproducible in children. 14 (14), vaso-occlusive (14), PPD (9), non-inflammatory purpura (6), interface dermatitis (5), neutrophilic dermatosis (4), cryoglobulinemia (1), EN (1), LV (1) and MVV (1).…”
Section: Relevance Of Non-iga Immunoreactants In Patients With Suspmentioning
confidence: 79%
“…Moreover, other groups have studied the presence of immunoglobulins in organ deposits. IgM has been associated with IgA skin deposits in children [ 17 ] and nephritis in adults [ 18 20 ]. IgG deposition in the kidney was associated with the nephritis outcome in adult IgAV patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%